PERSONAL HYGIENE DENGAN KEJADIAN DEMAM THYPOID BERULANG PADA PASIEN DI RUANG DAHLIA RSUD NGANJUK - Fatimah, Nur Aini; Widiyatmoko, Ilham Nova; Wahyudi, Heru; Rukmawati, Sefrina (LPPM STIKes SATRIA BHAKTI NGANJUK, 2021)
Typhoid fever is easily transmitted and can be affect to many people. Some patients with typhoid fever become carriers and are at risk of recurring typhoid fever. Typhoid fever is closely related to personal hygiene. The study design using correlational analytic with a retrospective approach. Results of Exact Fisher statistic test showed that the p-value = 0.015.